TINGKAT PENERAPAN PENGELOLAAN TANAMAN TERPADU (PTT) PADI DI KABUPATEN GARUT - Rahmawati, Fitri; Febrianti, Tintin; Gumelar, Asep Permadi (Jurusan Agribisnis, Fakultas Pertanian, Universitas Siliwangi, 2024)
The purpose of this study was to determine the level of implementation of Integrated Crop Management (PTT) of rice in Garut Regency. The location of the study is in Samarang Village, Samarang District, Garut Regency which will be carried out from July to August 2023. This research method is a survey method, data collection using questionnaires and interviews structured using ordinal measuring scales. Sampling by purposive sampling, the number of samples used was 30 rice farmers. The results of this study found that the application of rice PTT in three subsystems, namely the subsystem of providing production facilities, the cultivation subsystem, and the post-harvest subsystem is categorized as medium, in the application of rice PTT, farmers do it still not according to the recommendations that have been given.Keywords: Application, Integrated Crop Management (PTT), Rice